Plan estratégico de marketing para la empresa Artefacta agencias Quevedo El Empalme y Buena Fe periodo 2014 - 2016. - Sevillano Balcazar, Brarly Douglas (2015)
This research has been focused on the implementation of a Strategic Marketing Plan in Artefacta Company in the cities of Quevedo, Buena Fe and El Empalme, which make up the regional Quevedo, for the project a market survey was conducted and He established the need to implement the said plan. Based on the information collection company, analysis of micro and macro environment it was developed, for which several tools are used to have a clear concept and know what are the advantages and disadvantages of regional Artefacta Quevedo market stores Ecuador appliances. Considering the guidelines and established company such as vision, mission, policies, programs and procedures, all information for the best possible outcome meeting as there are no previous records of Strategic Planning appliances stores and Quevedo its zone of influence. Based on marketing objectives for which this Strategic Plan was proposed, it filled a large information gap regarding this issue were investigated both primerias secondary sources for the content of this project has its best purpose is ie serve as a guide for students and professionals of Marketing.